Micoteca da Universidade do Minho (MUM): implementation of a quality management system based on ISO 9001:2008 - Simões, Marta Filipa Jesus Freitas (2012)
[Excerpt] Micoteca da Universidade do Minho (MUM) is a filamentous fungi culture collection established in May 1996, hosted by the Biological Engineering Centre, which is a centre of excellence integrated in the Institute for Biotechnology and Bioengineering (IBB).The mission of MUM is to provide the highest quality services to our customers, collecting, maintaining and supplying fungal strains and their associated information for teaching and research in biotechnology and life sciences. MUM intends to be a centre of knowledge, information and training in mycology, operating at a global level and under national and international regulations. In order to keep its high standards MUM has implemented a Quality Management System (QMS) based on the normative reference ISO 9001:2008.MUM has defined three processes, those being: Material Reception Process, Material Preservation Process and Material Supply Process; and has also developed a documental base for all the QMS including proceedings, standard operating procedures, forms, as well as quality objectives and goals for a continuous improvement.